Causes of Juxta-cervical fistula, difficulties faced during repair and repair outcome: 52 cases - Begum, Bilkis; Akhter, Sumayia; Haider, Zinnat Ara (Journal of Surgical Sciences, 2021)
Genitourinary fistula in the region of the cervix is termed as juxta-cervical fistula. This is more common in multiparous individuals, especially those who voluntarily bear down before full cervical dilatation. Also frequently seen after caesarean delivery. But local harmful indigenous treatment in the genital area for genitourinary prolapse or any other reason should be kept in mind. Repair can be done vaginally, abdominally or sometimes may need a combined method. During surgery, less difficulties are felt if both the proximal and distal fistula margins are easily visible. Always precaution should be taken during lateral dissection towards the cervix to avoid ureteric injury. Journal of Surgical Sciences (2021) Vol. 25(2) : 31-36